Liposomes as drug delivery: A review of innovations in disease treatment and tumor therapy - Pereira, Arthur van Lauter Albuquerque; Yara, Ricardo; Junior , Silvio Marçal de Vasconcelos; Amorim, Rosa Valéria da Silva (Seven Editora, 2024)
Liposomes are a drug delivery model that are studied for the treatment of various pathologies. These nanoparticles are manufactured by redirecting phospholipids with the hydrophilic inner medium surrounded by the lipophilic bilayer. As an additional advantage of this model, several changes can be made to the bilayer to implement the transport of drugs in the biological media, such as the insertion of polyethylene glycol, peptides and carbohydrates, giving more specificity to the drug delivery model, such as multifunctional liposomes and ligand-directed liposomes. These modifications help in the different mechanisms of active and passive vectorization and make the liposome system cover several areas of action, such as pain control, antibacterial action, and vaccines. In addition, these nanoparticles are also used in new strategies in tumor therapy, which use cancer symptoms to target nanoparticles more effectively, such as double-ligand liposomes, co-delivery liposomes, and sensitive to stimuli that are still under development or already used in the clinic. DOI:https://doi.org/10.56238/sevened2024.025-016